2008
DOI: 10.1177/183693910803300110
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Child Care—Leading the Way

Abstract: We believe that the Australian early childhood sector is not performing well. The incidence of poor outcomes for children is increasing, and we believe that current service delivery is not capable of addressing this. We argue that, as a sector, there is an abundance of evidence of the kinds of programs and initiatives that could address our national concerns, and review some of that evidence. We also point out that there is considerable knowledge in Australia, based on Australian programmes and experience, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Services have been developed to address the overall developmental burdens of poverty as well as the impacts of specific adversities, such as maternal depression (Cicchetti, Rogosch, & Toth, 2000; Nylen, Moran, Franklin, & O'Hara, 2006) and involvement in the child welfare system as a result of child maltreatment (Pears, Fisher, & Bronz, 2007; Pears, Kim, & Fisher, 2012). Programs targeting the distinctive strengths and needs of different racial and ethnic groups have also been developed, with a particular focus on the importance of addressing issues of cross-cultural competence and the damaging effects of discrimination on human development (Klingner et al, 2005; Sims et al, 2008). Detailed descriptions of these diverse categories of program models and intervention strategies are beyond the scope of this paper.…”
Section: Flagship Models Benefit–cost Analyses and The Enduring Chamentioning
confidence: 99%
“…Services have been developed to address the overall developmental burdens of poverty as well as the impacts of specific adversities, such as maternal depression (Cicchetti, Rogosch, & Toth, 2000; Nylen, Moran, Franklin, & O'Hara, 2006) and involvement in the child welfare system as a result of child maltreatment (Pears, Fisher, & Bronz, 2007; Pears, Kim, & Fisher, 2012). Programs targeting the distinctive strengths and needs of different racial and ethnic groups have also been developed, with a particular focus on the importance of addressing issues of cross-cultural competence and the damaging effects of discrimination on human development (Klingner et al, 2005; Sims et al, 2008). Detailed descriptions of these diverse categories of program models and intervention strategies are beyond the scope of this paper.…”
Section: Flagship Models Benefit–cost Analyses and The Enduring Chamentioning
confidence: 99%
“…In the Australian context, this body of evidence has been the catalyst for increased investment in ECEC programs and a strategy directed towards closing the equity gap between Indigenous and non-Indigenous Australians (COAG, 2009a(COAG, , 2009b). Yet, uptake of ECEC by Indigenous families has remained lower than that for non-Indigenous Australians (Taylor, 2010) and enrolments in programs by Indigenous families have not been matched by continuity of attendance (Sims et al, 2008). For many, access to ECEC programs is obstructed by a complexity of personal and cultural factors and systemic constraints (Jackiewicz, Saggers & Francis, 2011;Trudgett & Grace, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These latter considerations by Sims et al (2008a;2008b) are particularly relevant for the study reported here. The location of the proposed centre in an iconic place for Aboriginal people in Western Australia is a key component of the consultation process.…”
Section: Recognition Of Indigenous Community Kinshipmentioning
confidence: 69%
“…Further, they identify seven strengthsbased capacity-building service areas for Aboriginal families and children. These areas are: nutrition, health, transport, play and leisure, early learning and development, cultural program, and family support (Sims et al, 2008a). They note that:…”
Section: Integrated Family and Children's Services For Australian Abomentioning
confidence: 99%